A Drop in the Ocean - Tinna Guðmundsdóttir 1979- (2022)
This thesis addresses my most recent artistic projects and is an attempt to dissect the artistic process behind them. Artmaking has been an integrated part of my life for two decades. Alongside I have worked as an art practitioner in Iceland, for the most part in a grassroot institutional venue in a tiny rural community. My role there was very culturally important and affected the town on many levels, from widening the perspective of children in the region and connecting international artists to the Icelandic art scene. To have upheld a service role has formalised me and found its way into my artwork. My practice has been mostly based on subconsciously developed methods and techniques, manifesting in photography and three-dimensional work. Many of my projects have had a very precise structure and defined form or shape, based on formalistic elements. The working process often consists of working within a timeframe as well as a specific material and sometimes from certain geological locations. The artistic framework I have been working within has distinct and clearly defined rules. Rules provide limitations, and within those limitations there is creative space to explore. The downside of approaching artmaking in this way was that I had found that the practice had become restricting and overwhelming at times. Through my studies I have been on the voyage of redefining my practice, and during that process I have struggled with articulation, both in writing and verbal presentation. When I was starting this thesis, I was asked by my advisor what my expectations were towards it. I replied that I wanted to find my voice, meaning how to communicate in words with my own vocabulary of what, how and why. Therefore, I wanted to use the thesis as a tool to practice different ways of describing, explaining and/or supporting my artistic tests, explorations, and outcome. Throughout the writing phase I have been navigating through an ocean of words and texts, looking for a clear and understandable way I can present the practice ...